Application of PSMA PET/CT Specific Molecular Imaging in Diagnosis of Non-prostate Cancer - LIU Teli (Zhongliu Fangzhi Yanjiu, 2019)
Prostate specific membrane antigen(PSMA) is a glutamate carboxypeptidase Ⅱ secreted by the epithelial cells of prostate gland. PSMA is over-expressed in the cells of prostate cancer and metastases, and also positively expressed in the tumor-related neovascular endothelial cells. Therefore, more than twenty PSMA-targeted probes had been used for the diagnosis and therapy of prostate cancer. This article reviews the expression of PSMA in non-prostate cancer and the clinical application of PSMA-PET/CT specific probes in detecting non-prostate cancer, to expand the clinical application of novel PSMA-targeted PET probes in the diagnosis of tumors.